Study the Factors Effective on the Success of Rural Entrepreneurs in the Rural Areas of Ardabil Province - Vakil Heidari Sarban (جغرافیا و توسعه, 2015)
Entrepreneurship as a process, system and strategy, not only creates employment for widespread community of rural areas but also through  reinforcement of skills and capacity of local community will change the  rural's  income. The purpose of the present study was to investigate of rural entrepreneurs in the rural area of Ardabil province.  The research method is a descriptive-analytical study of the survey type. The target population in the study is the entrepreneurs of rural in Ardabil Province. Using simple random sampling technique,  90 rural entrepreneurs were selected as the statistical society . The content of the questionnaire was specified after several times  of review and correction by the faculty of members of the  university and several expertise of administrative offices. The reliability analysis was conducted and Cronbach’s alpha values for the various sections of instrument were estimated to be between 0.81 and 0.87.At the end, results showed that the most important effective factors on rural entrepreneurs success in the rural areas are six components such as (empowerment and  reinforcement of economical and legal infrastructures and information technology, reinforcement of  motivation and agricultural commercialization, institutionalism and capacity increase , strengthening  of social participation and accumulation of separated  rural areas  ) that the variance and explained accumulated variance number is (88.07) via this six factors.